THE EFFECTIVENESS OF THE PROBLEM-BASED LEARNING MODEL ASSISTED BY GEOGEBRA ON JUNIOR HIGH SCHOOL STUDENTS MATHEMATICS LEARNING OUTCOMES IN SOLID GEOMETRY - Rahma Nasir; Mustamin Idris; Amrah Hazanah; Alfisyahra Alfisyahra (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aims to determine the differences in the average learning outcomes of students taught using the Problem-Based Learning (PBL) model assisted by GeoGebra and those taught using direct instruction on the topic of three-dimensional geometry in Grade IX. The research was motivated by the low student achievement, which is caused by difficulties in understanding the properties of three-dimensional shapes as well as limitations in the use of media and the application of less appropriate teaching models. This study is a quantitative research with a Quasi-Experimental approach, specifically the nonequivalent control group design. The research sample consisted of 128 students, divided into two experimental classes and two control classes, selected through random sampling techniques. The data collection instrument was a test administered in the form of pretest and post-test, which had been validated by experts. Descriptive analysis results showed that the average post-testÂ scores in the experimental classes (80.69 and 78.63) were higher than those in the control classes (74.38 and 73.28). The hypothesis testing using the independent sample t-test indicated a significance value of 0.000 < 0.05, thus it can be concluded that there is a significant difference between the average learning outcomes of students in the two groups. Furthermore, the N-gain analysis results showed that the improvement in learning outcomes in the experimental classes was 0.47 (medium category), which was higher than that in the control classes at 0.36. Therefore, the PBL model assisted by GeoGebra is effective in improving studentsâ€™ mathematics learning outcomes on the topic of three-dimensional geometry.Keywords: problem-based learning, GeoGebra, learning outcomes, three-dimensional shapes.